2008
DOI: 10.1614/ipsm-08-080.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Triclopyr andMycoleptodiscus terrestrisfor Control of Eurasian Watermilfoil (Myriophyllum spicatum)

Abstract: Growth chamber studies were conducted using 55-L aquariums to evaluate the efficacy of the herbicide triclopyr and the fungal pathogenMycoleptodiscus terrestris, applied alone and in combination against Eurasian watermilfoil. Treatments included 0.15, 0.40, and 1.50 mg acid equivalent (ae)/L triclopyr, 0.08, 0.16, and 0.32 ml/LM. terrestris, combinations of both agents at all rates, and an untreated control. Plants were exposed to all treatments for a 24-h contact time and plant biomass (shoot and roots) was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
(18 reference statements)
0
10
0
2
Order By: Relevance
“…Trabalhos realizados por diferentes pesquisadores comprovam a eficácia do controle químico nessas plantas flutuantes e sua segurança sobre organismos aquáticos por meio do uso de diversos herbicidas, como 2,4-D (Joyle & Sikka 1977;Selvan & Lall, 1981;Martins et al, 1999Martins et al, , 2002Nelson & Shearer, 2005), glyphosate (Van et al, 1987;Martins et al, 1999Martins et al, , 2002Neves et al, 2002;Lindgren et al, 1999;Fairchild et al, 2002), diquat (Martins et al, 1999(Martins et al, , 2002, imazapyr (Martins et al, 1999(Martins et al, , 2002, carfentrazoneethyl (Koschnick et al, 2004), entre outros.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Trabalhos realizados por diferentes pesquisadores comprovam a eficácia do controle químico nessas plantas flutuantes e sua segurança sobre organismos aquáticos por meio do uso de diversos herbicidas, como 2,4-D (Joyle & Sikka 1977;Selvan & Lall, 1981;Martins et al, 1999Martins et al, , 2002Nelson & Shearer, 2005), glyphosate (Van et al, 1987;Martins et al, 1999Martins et al, , 2002Neves et al, 2002;Lindgren et al, 1999;Fairchild et al, 2002), diquat (Martins et al, 1999(Martins et al, , 2002, imazapyr (Martins et al, 1999(Martins et al, , 2002, carfentrazoneethyl (Koschnick et al, 2004), entre outros.…”
Section: Introductionunclassified
“…Entretanto, alguns desses trabalhos também relatam controles insatisfatórios, os quais provavelmente podem ser atribuídos à falta de contato apropriado da calda pulverizada com as plantas (Martins et al, 2002;Neves et al, 2002). Nesse sentido, o tipo de ponta utilizada na pulverização e o arranjo entre as espécies presentes na população podem influenciar a quantidade dos depósitos de calda pulverizada sobre as plantas de salvínia, uma vez que a posição do limbo foliar, em relação à posição do limbo foliar das plantas vizinhas, pode Deposição de calda de pulverização sobre plantas de salvínia ... favorecer ou prejudicar o contato entre a gota e a superfície foliar.…”
Section: Introductionunclassified
“…tion Dr. Judy Shearer, 2005). It was considered to be a promising biocontrol candidate for EWM and early greenhouse and laboratory studies showed that Mt reduced milfoil biomass (Gunter et al 1990, Stack 1990, Smith and Winfield 1991.…”
Section: General Information and Historymentioning
confidence: 99%
“…Other research being conducted by Drs. Judy Shearer and Linda Nelson (ERDC, Vicksburg, MS) integrates Mt with the herbicides fluoridone, endothall, and 2,4-D (Nelson et al 1998, Nelson and Shearer 2005 to observe whether there is improved activity with the combination of pathogen and herbicide for aquatic plant management as opposed to using either method independently. Earlier work done by Netherland and Shearer (1996), demonstrated a potential for combining the two technologies, chemical and biological control, for the management of hydrilla.…”
Section: Research/impactmentioning
confidence: 99%
“…Microsclerotia of M. terrestris formed hyphae (hyphal germination) and conidia (sporogenic germination) that were capable of infecting and killing hydrilla Jackson 2003, 2006;Shearer 2007). Mycoleptodiscus terrestris has been extensively studied as a bioherbicide for aquatic weeds but remains to be fully developed as a commercial control tool for hydrilla management (Netherland and Shearer 1996;Shearer and Nelson 2002;Nelson and Shearer 2008). Evaluations of hydrilla control with fresh, liquid culture preparations of M. terrestris showed a correlation between colony forming units (cfu) and hydrilla infectivity and control with significant reductions in hydrilla biomass using application rates of 100 cfu L (1 (Shearer and Nelson 2002).…”
Section: Introductionmentioning
confidence: 99%